Metabolomics-Enhanced Gas Chromatography Mass Spectrometry (GC-MS) For The Quality Standardisation Of Clinacanthus Nutans - Baharom, Nabilah Hanim (2017)
Clinacanthus nutans, a widely used medicinal plant, is extensively grown in tropical Asia and Southest Asian countries. C. nutans with its broad spectrum of pharmacological activities has been traditionally used to treat cancer, inflammatory disorders, diabetes, insect bites and skin problems